The ECHR at 70: The Central European Narrative (Studies of the Central European Professors’ Network, 2025)
The ECHR entered into force on 3 September 1953, and since then, Europe has gone through countless changes and faced scores of challenges: Environmental problems, the changes of regime in post-socialist States, the conquest of the internet, migration, the COVID-19 pandemic, the Russian-Ukrainian war etc. No wonder, in the era of ever evolving societies, one might easily raise the question: How can a 70-year-old convention provide effective protection for human rights and how can it still work as a living instrument? The aim of the volume is to demonstrate the indisputable reactivity and modernity of the ECHR putting an emphasis on the ECtHR’s interpretation techniques and focusing on Central European countries.